MAGNETIC RESPONSE OF LOCAL MOMENTS IN DISORDERED METALS - Rowan, D; Szczech, Y; Tusch, M; Logan, D (1995)
We study the magnetic response properties of both site and spatially disordered Anderson-Hubbard models via a random-phase-type approximation for collective excitations about stable, inhomogeneous mean-field ground states. For the site-disordered model, zero-temperature transitions between paramagnetic, disordered antiferromagnetic and spin-glass-like ground states are examined. Within broken symmetry phases, a microscopic picture of the response of the inhomogeneous distribution of local magnetic moments to an external field is obtained, and the role of disorder in leading to a strong site differential enhancement in local susceptibilities is highlighted.